Surface functionalized magnetic nanoparticles shift cell behavior with on/off magnetic fields. Issue 2 (7th June 2017) - Jeon, Seongbeom; Subbiah, Ramesh; Bonaedy, Taufik; Van, Seyoung; Park, Kwideok; Yun, Kyusik
Abstract : Magnetic nanoparticles (MNPs) are used as contrast agents and targeted drug delivery systems (TDDS) due to their favorable size, surface charge, and magnetic properties. Unfortunately, the toxicity associated with MNPs limits their biological applications. Surface functionalization of MNPs with selective polymers alters the surface chemistry to impart better biocompatibility. We report the preparation of surface functionalized MNPs using iron oxide NPs (MNPs), poly (lactic‐co‐glycolic acid) (PLGA), and sodium alginate via co‐precipitation, emulsification, and electro‐spraying, respectively. The NPs are in the nanosize range and negatively charged. Morphological and structural analyses affirm the surface functionalized nanostructure of the NPs. The surface functionalized MNPs are biocompatible, and demonstrate enhanced intracellular delivery under an applied magnetic field (H), which evinces the targeting ability of MNPs. After NP treatment, the physico‐mechanical properties of fibroblasts are decided by the selective MNP uptake under "on" or "off" magnetic field conditions. We envision potential use of biocompatible surface functionalized MNP for intracellular‐, targeted‐DDS, imaging, and for investigating cellular mechanics. Abstract : Bio‐chemico‐physico‐mechanics. PLGA/Alginate based core‐shell (C‐S) magnetic nanoparticles (MNP) impart better biocompatibility. Magnetic field promotes forcible intracellular uptake of C‐S MNP, stiffness changes of cells and we envision potential use of biocompatible C‐S MNP for intracellular‐, targeted‐DDS, imaging, and for investigating cellular mechanics.